PENGENDALIAN KUALITAS SARANG BURUNG WALET DI CV LVS PROBOLINGGO DENGAN MENGGUNAKAN NEW SEVEN TOOLS - Pricilia Himawan; Siti Rahayu; Stefanus Budy Widjaja S. (CALYPTRA, 2018)
Based on the problems that exist in the company, the purpose of this study was to determine how to control the quality of birdnest at CV LVS Probolinggo using the New Seven Tools to minimize defects that occur. New Seven Tools method begins by identifying the root causes of the company and then assign efforts to find a solution that could be done by the company. In this study, the tools used were affinity diagram,relation diagram, tree diagram, matrix diagram, priority matrix, arrow diagram danprocess decision program chart (PDPC).